Pengembangan Komik Edukasi Detektif Sains Sebagai Media Pembelajaran Literasi Sains Sekolah Dasar - Oryzasativa, Tristaoryza; Sari, Tita Tanjung; Kadarisman (Jurnal Ilmu Pendidikan Dasar Indonesia, 2023)
Currently, the learning concept used in realizing 21st-century learning is that students need media or facilities in learning activities to become fun. Educational comics are an alternative used as learning media to improve the quality of education for the better. This study uses the R & D (Research and Development) research method with the research stage of the Borg and Gall model, which has been modified by Sugiono and consists of 7 research stages due to time, cost, and also the impact of the co-19 pandemic. This study aims to: (1) describe the development of the educational comic "Science Detective" as a learning medium and (2) find out students' responses to the development of the educational comic "Science Detective" as a learning medium. The subjects of this study were fifth-grade elementary school students. The instruments in this study were product validation instruments and student responses, while the data analysis scale used was the Likert scale and Guttman scale. In making it, the applications used are Medibangpaint Photoshop CS3 and Canva. The results of the research show that: (1) the development in this study was declared fit for use as learning media; this was based on the validation of media and material designs with successive percentages of 94% and 92% with the criteria of "Very Appropriate" and "Not Revised". (2) the results of student responses or product trials of 8 elementary school students obtained a score with a percentage of 95% with the "Very Good" criterion. So it can be concluded that the educational comic learning media "Science Detective" can be declared feasible and suitable for alternative learning media.